Photosynthetic characteristics of charophytes from tropical iotic ecosystems - Vieira Jr., Jair [UNESP]; Necchi Jr., Orlando [UNESP] (My University, 2003)
Responses of photosynthetic rates, determined by oxygen evolution using the light and dark bottles technique, to different temperatures, irradiances, pH, and diurnal rhythm were analyzed under laboratory conditions in four charophyte species (Chara braunii Gmelin, C. guairensis R. Bicudo, Nitella subglomerata A. Braun and Nitella sp.) from Iotic habitats in southeastern Brazil. Parameters derived from the photosynthesis versus irradiance curves indicated affinity to low irradiances for all algae tested. Some degree of photoinhibition, [β = -(0.30-0.13) mg 02 g-1 dry weight h-1 (μmol photons m-2 s-1)-1], low light compensation points (lc = 4-20 μmol photons m-2 s-1) were found for all species analyzed, as well as low values of light saturation parameter (lk) and saturation (ls) 29-130 and 92-169 μmol photons m-2 S-1, respectively. Photoacclimation was observed in two populations of N. subglomerata collected from sites with different irradiances, consisting of variations in photosynthetic parameters (higher values of α, and lower of lk and maximum photosynthetic rate, Pmax, in the population under lower irradiance). The highest photosynthetic rates for Chara species were observed at 10-15°C, while for Nitella the highest photosynthetic rate was observed at 20-25°C, despite the lack of significant differences among most levels tested. Rates of dark respiration significantly increase with temperature, with the highest values at 25°C. The results from pH experiments showed highest photosynthetic rates under pH 4.0 for all algae, suggesting higher affinity for inorganic carbon in the form of carbon dioxide, except in one population of N. subglomerata, with similar rates under the three levels, suggesting indistinct use of bicarbonate and carbon dioxide. Diurnal changes in photosynthetic rates revealed a general pattern for most algae tested, which was characterized by two peaks: the first (higher) during the morning (07.00-11.00) and the second (lower) in the afternoon (14.00-17.00). This suggests an endogenous rhythm determining the daily variations in photosynthetic rates.
Keywords: Charophytes; Diurnal rhythm; Irradiance; PH; Photosynthesis; Temperature; circadian rhythm; irradiance; macrophyte; photosynthesis; tropical environment; Brazil; algae; Chara braunii; Chara guairensis; Characeae; Charales; Eukaryota; Halophila; Nitella sp.; Nitella subglomerata